1969
DOI: 10.2307/3895869
|View full text |Cite
|
Sign up to set email alerts
|

How Time and Intensity of Clipping Affect Tall Bluebell

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

1972
1972
2004
2004

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…These include bluebell (Mertensia arizonica var. Zeonardi) (Laycock and Conrad, 1969) (Julander, 1968).…”
Section: Effects Of Clipping Discussionmentioning
confidence: 99%
“…These include bluebell (Mertensia arizonica var. Zeonardi) (Laycock and Conrad, 1969) (Julander, 1968).…”
Section: Effects Of Clipping Discussionmentioning
confidence: 99%
“…By artificially flattening the stems of tall bluebell (Mertensia arizonica var. leonardi) during the early flowering and fruiting stages for 4 consecutive years, Laycock and Conrad (1969) found that herbage production was reduced by approximately 50%. Similar studies for other species are needed to clarify the effect of trampling upon herbage production and vigor.…”
Section: Trampling Lossesmentioning
confidence: 96%
“…Consequently, highly palatable, late -seral forb species can be eliminated from plant communities with little or no change in range condition scores and recommended stocking rates. Published studies of defoliation effects on vigor and/or population dynamics of forb species are uncommon (Julander 1968;Laycock and Conrad 1969;Inouye 1982;Reichman and Smith 1991;Gronemeyer et al 1997) and rare for forbs in grass-dominated ecosystems (Hartnett 1990;Vermeire and Gillen 2000;Damhoureyeh and Hartnett 2002;Hickman and Hartnett 2002).…”
Section: Introductionmentioning
confidence: 99%